The determinants of accounting comparability around the world. Issue 1 (22nd November 2019) - Ross, Jonathan; Shi, Linna; Xie, Hong
Abstract : Purpose: The purpose of this paper is to investigate country-level and firm-level determinants of within-country accounting comparability for 16 European Union countries plus the USA in the post-International Financial Reporting Standards adoption period. Design/methodology/approach: The authors use ordinary least squares regression to test the hypotheses with a correction for heteroscedasticity. Findings: The authors find that firms in countries with rules-based accounting, higher quality public auditor work environments, stricter enforcement of accounting standards and more reliance on equity-market financing have higher within-country comparability with each other. At the firm-level, the authors find that firms which are larger, engage in less earnings management, and have lower return-on-asset volatility have higher within-country comparability with each other. Research limitations/implications: The authors use one measure of accounting comparability. Alternative measures of accounting comparability could test the hypotheses more completely. Practical implications: The findings of the paper may help the regulators make more efficient policies to establish an efficient financial market within their country. Originality/value: The paper is the first, to the authors' knowledge, to identify country-level and firm-level determinants of within-country accounting comparability. It contributes to the accounting literature by completing the theory of international accounting comparability from the within-country perspectives, as prior literature focuses on the cross-country perspective of international accounting comparability.